Gadolinium enhancement of the leptomeninges caused by hydrocephalus: a potential mimic of leptomeningeal metastasis. - Schumacher, D J; Tien, R D; Friedman, H (American Journal of Neuroradiology, 1994)
A patient had severe hydrocephalus and diffuse leptomeningeal enhancement on MR which mimicked leptomeningeal spread of a primary brain tumor. The leptomeningeal enhancement resolved completely after decompression of the hydrocephalus. Data suggest that the leptomeningeal enhancement is caused by vascular stasis induced by the hydrocephalus.